Faktor-Faktor Yang Memengaruhi Kepuasan Pemustaka Terhadap Layanan Perpustakaan Puslitbang Perkebunan Badan Litbang Pertanian, Kementerian Pertanian - Erriani Kristiyaningsih (Media Pustakawan, 2020)
Library services are one of the main activities of libraries to utilize their collections to users as well as government-owned libraries that focus on library service satisfaction. The purpose of this study was to analyze the Factors Affecting Service Satisfaction in the Agriculture Library of the Ministry of Agriculture. The study was conducted on visitors to the agricultural library of the Ministry of Agriculture. The number of respondents selected is as many as 100 people selected based on the method of accidental sampling. Data analysis was performed descriptively and using ordinal regression. The results obtained that the timeliness of service, SOP conformity of service products, and the quality of facilities and infrastructure have a significant effect on customer service satisfaction.